IMPLEMENTATION OF COBIT 2019 TO MEASURE IT MATURITY LEVELS IN DIGITAL BANKS - Rahmat Rian Hidayat; Jatikusumo, Dwiki (Jurnal Teknik Informatika (Jutif), 2024)
As a bank supervised by authorities such as the Financial Services Authority (OJK), however, Bank ATR must improve its digital maturity in accordance with the criteria of the OJK Digital Banking Transformation Blueprint. The blueprint has not yet established a method to measure the digital maturity. As a result, the banking industry is having difficulty meeting these requirements. This study aims to measure the level of capability and provide recommendations for improvement using the COBIT 2019 framework. This study uses a qualitative method approach with the COBIT 2019 framework and data collection techniques through interviews. The results of the study show that the level of IT maturity at Bank ATR is 2.76 (Managed). This shows that the Bank's IT management produces a level of process capability that has achieved its goals by carrying out activities that are carried out regularly, while EDM objective management gets the highest maturity with 4.0, and APO objective management gets the lowest maturity with 2.0.